Follow-Up of Blood Pressure, Arterial Stiffness, and GFR in Pediatric Kidney Transplant Recipients - Végh, Anna; Bárczi, Adrienn; Cseprekál, Orsolya; Kis, Éva; Kelen, Kata; Török, Szilárd; Szabó, Attila J.; Reusz, György S. (Frontiers in Medicine, 2021)
Pediatric renal transplant recipients (RTx) were studied for longitudinal changes in blood pressure (BP), arterial stiffness by pulse wave velocity (PWV) and graft function. Patients and methods: 52 RTx patients (22 males) were included; office BP (OBP) and 24h BP monitoring (ABPM) as well as PWV were assessed together with glycemic and lipid parameters and glomerular filtration rate (GFR) at 2.4[1.0-4.7] (T1) and 9.3[6.3-11.8] years (T2) after transplantation (median [range]). Results: hypertension was present in 67% and 75% of patients at T1 and T2, respectively. Controlled hypertension was documented in 37% and 44% by OBP and 40% and 43% by ABPM. Nocturnal hypertension was present in 35% and 30% at T1 and T2; 24% and 32% of the patients had masked hypertension, while white coat hypertension was present in 16% and 21% at T1 and T2, respectively. Blood pressure by ABPM correlated significantly with GFR and PWV at T2, while PWV also correlated significantly with T2 cholesterol levels. Patients with uncontrolled hypertension by ABPM had a significant decrease in GFR, although not significant with OBP. Anemia and increased HOMAi were present in approximately 20% of patients at T1 and T2. Conclusion: pediatric RTx patients harbor risk factors that may affect their cardiovascular health. While we were unable to predict the evolution of renal function based on PWV and ABPM at T1, these risk factors correlated closely with GFR at follow-up suggesting that control of hypertension may have an impact on the evolution of GFR.